Face Gender Classification for Public Facility Access Control using EfficientNet with Penalized-Entropy Loss - Sari, Sabrina Adinda; Ramadhan Ahmad, Faidhil Nugrah; Adnan Rasyid, Miftahul; Manggala Putra, I Gede; Ramadhan, Fauzan (Jurnal Teknik Informatika (Jutif), 2026)
Access to public facilities that are restricted based on gender, such as toilets and changing rooms, requires a strict security system because there are still many cases of abuse by irresponsible parties if only gender signs are relied upon. CCTV integrated with facial recognition is becoming more sophisticated every day, but it is limited if the face is covered by attributes such as masks. This is because the less visible the area is, the more difficult it is for the model to determine the label. To overcome this, this study proposes a gender classification approach for faces that may be covered by accessories such as masks, by adding Penalized Entropy loss as a loss function to the EfficientNet-B0 model. This loss function adds a penalty for incorrect predictions even if they are fairly accurate. The evaluation results show that the proposed model, with a penalty weight of 0.5, improved the accuracy by 3% from 90% to 93%.  The experimental results show that the determination of the penalty weight has a significant impact on model performance, where a weight of 0.5 produces optimal performance because it provides a balance between penalizing overconfident predictions and the model's ability to maintain relevant feature discrimination; too small a weight does not sufficiently suppress overconfidence, while too large a weight actually reduces classification ability. The proposed method has demonstrated improvements in generalization and reduced overconfidence in gender classification systems. This method contributes to the development of reliable biometric systems suitable for uncontrolled real-world environments.